Microstructures of the spermatic cord with three-dimensional reconstruction of sections of the cord and application to varicocele. (3rd May 2020) - Yang, Yu; Wu, Xiaoqiang; Leng, Qu; Su, Wei; Wang, Shuo; Xing, Rongwei; Zhou, Xumin; Lv, Daojun; Li, Bingkun; Mao, Xiangming
ABSTRACT: The aim of the study was to investigate the micro-structures of the spermatic cord using histological examination with three-dimensional (3D) reconstruction of the serial tissue sections of the cord for clinical application in microscopic varicocelectomy. Human spermatic cord specimens obtained from 13 adult male cadavers were used to prepare serial transverse sections. The sections were stained to allow observation of the spermatic cord microstructures. The 3D reconstruction was performed with digitized serial sections by Mimics software. The microscopic varicocelectomy was performed based on the anatomical results of 3D reconstruction of the spermatic cord. The results showed the number of small spermatic veins, large spermatic veins, arteries, lymphatics or nerves were not markedly different between the subinguinal and inguinal regions or between the right and left sperm cord. The number of medium spermatic veins in the subinguinal region was obviously higher than at the inguinal level. The internal spermatic vessels and the vas deferens together with other associated vessels within the cremaster were separately enclosed by two thin and translucent sheaths, the internal spermatic fascia and the vas deferens fascia. We conclude that internal spermatic vessels and the vas deferens together with the associated neurovascular vessels are wrapped by two distinct sheaths separating them from the surrounding tissues. Microscopic varicocelectomy based on the anatomical results of 3D reconstruction of the spermatic cord is feasible. Abbreviations: 3D: three-dimensional; ISF: internal spermatic fascia; ESF: external spermatic fascia; MHIV: High inguinal microsurgical varicocelectomy; MSIV: subinguinal microsurgical varicocelectomy; CAAD: computer-assisted anatomic dissection; HE: hematoxylin-eosin